Investigation on motorcyclist riding behaviour at curve entry in the down slope terrain - Yuen, C.W.; Karim, M.R.; Saifizul, A. (Springer Verlag (Germany), 2015)
Motorcyclists are considered a very vulnerable group of road users as far as road accidents are concerned. Safety of this form of transportation is an important issue. This paper details the study on the changes in riding behaviour, such as changes in speed as well as brake force and throttle force applied, when motorcyclists ride over a curve section road using an instrumented motorcycle. In this study, an instrumented motorcycle equipped with various types of sensors, on-board cameras and data loggers, was developed in order to collect the riding data on the study site. Results from the statistical analysis showed that riding characteristics such as changes in speed, brake force and throttle force applied, are influenced by the distance from the curve entry, riding experience and travel mileage of the riders. A structural equation modeling was used to study the impact of these variables towards the change of riding behaviour in curve entry section. Three regression equations are formed to study the relationship between three dependent variables, which are speed, throttle force and brake force applied with the independent variables. In short, riders tend decelerate to achieve a comfortable speed, by applying higher brake intensity and release throttle force, when they ride closer to the curve section.